The forest farmers' mindsets contribution to ecosystem degradation in Meru Betiri National Park, Indonesia: towards sustainable conservation through a translation practices approach - Ikhsan, Fahrudi Ahwan; Sumarmi, Sumarmi; Utaya, Sugeng; Sugiarto, Agus; Heldayani, Eni (Journal of Degraded and Mining Lands Management, 2026)
Controlling land degradation in conservation areas requires improvement, especially given the spatial impacts of human-environment interactions within the Meru Betiri National Park Biosphere Reserve, Indonesia. Drawing upon geosystem theory, this study investigated land change issues stemming from human-environment interactions within Meru Betiri National Park's conservation area. This study adopted a mixed-methods design that incorporated field observations, surveys, and in-depth interviews. Quantitative data were obtained from observations of the degradation landscape and a survey of forest farmers, while qualitative data were collected through interviews with key observer participants. Data analysis was triangulated through a Forum Group Discussion (FGD) involving forest farmers and policymakers. The findings indicate that forest farmer conservation practices influence knowledge transformation, environmental education, and funding mechanisms. These elements are integral to a sustainable "translation approach" to restore the conservation area's ecological landscape. The impact of ecosystem restoration leads to significant spatial and contextual changes within the biosphere reserve's geosystem landscape. This study highlights the implications of the interplay among farmer thinking patterns, funding, and policies for enhancing welfare through a sustainable critical land conservation model. Applying this "translation approach" offers valuable spatial and temporal conservation insights in protected areas.